Transfection of the Giardia lamblia double-stranded RNA virus into giardia lamblia by electroporation of a single-stranded RNA copy of the viral genome. - Furfine, E S (1990)
The development of a genetic vector for protozoan parasites is a major hurdle yet to be crossed in the study of the molecular and cellular biology of these parasites. We have identified and isolated a double-stranded RNA virus (G. lamblia virus [GLV]) from certain strains of the intestinal parasitic protozoan Giardia lamblia (A. L. Wang and C. C. Wang, Mol. Biochem. Parasitol. 21:269-276, 1986), which is capable of infecting other virus-free strains of G. lamblia (R. L. Miller, A. L. Wang, and C. C. Wang, Exp. Parasitol. 66:118-123, 1988). Here we demonstrate that G. lamblia can be infected with GLV by electroporating uninfected cells with purified single-stranded RNA (E. S. Furfine, T. C. White, A. L. Wang, and C. C. Wang, Nucleic Acids Res. 17:7453-7467, 1989) representing a full-length copy of one strand of the GLV double-stranded RNA genome. To the best of our knowledge, this is the first demonstration in vivo that a single-stranded RNA is a competent replicative intermediate for this class of double-stranded RNA virus. In addition, this result represents the first long-term transfection of a protozoan by a single species of RNA and will hopefully expedite the development of GLV as a genetic transfecting vector.